Molecular sieve adsorbent as well as preparation method and application thereof
By preparing molecular sieve adsorption agents with excellent water resistance and carbon dioxide adsorption effect, the competition adsorption problem of molecular sieve in adsorption of water vapor and carbon dioxide has been solved, and high -efficiency carbon dioxide adsorption and compression resistance of water vapor conditions are realized.
Patent Information
- Application Number
- CN202411497808.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
During the air separation process, there is competitive adsorption when molecular sieve adsorption of water vapor and carbon dioxide, resulting in poor carbon dioxide adsorption effect.
By mixing the sodium -based X -type molecules, the bumpy rod soil and the pores, the spherical and roasting are performed to prepare molecular sieve adsorption agents with excellent water resistance and carbon dioxide adsorption effect.
Achieving excellent carbon dioxide adsorption performance under water vapor conditions, avoiding decreased performance of adsorbents under high temperature and high humidity conditions, and improving the tunnel structure of adsorption agents, enhancing its anti -expansion and compression performance.
Smart Images

Figure BDA0005101725910000091 
Figure BDA0005101725910000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a molecular sieve adsorbent and a preparation method and application thereof. Background Art
[0002] With the development of all walks of life, the demand for industrial gases, especially oxygen and nitrogen, which are called modern industrial gases, has increased dramatically. The industrial production of oxygen and nitrogen mainly comes from the separation of air. The main separation methods are low-temperature separation, pressure swing adsorption and membrane separation. Low-temperature nitrogen production can produce nitrogen with a purity of ≥99.999%, which has greater advantages than pressure swing adsorption and membrane separation. The principle is to use air as raw material, compress it through a compressor, purify it through an air purification device, and heat it through a heat exchanger to form liquid air. Then, by using the different boiling points of the components of the liquid air, they are continuously evaporated and condensed in a two-stage distillation tower to finally separate the components.
[0003] Air is a multi-component gas. In addition to the industrial gases required for production: nitrogen, oxygen and rare gases, it also includes impurities: carbon dioxide, water vapor. When separating air, the physical properties of each component must be taken into account. Once impurities enter the air separation system, it will reduce production efficiency and even cause safety accidents: carbon dioxide and water vapor will be the first to precipitate during the cooling process due to their high melting points. The precipitated crystals are constantly deposited in the exchanger, expander and distillation tower, which will eventually cause the transportation pipeline and valve to be blocked. Therefore, in industry, the raw air must be strictly pretreated before separation to remove water vapor and carbon dioxide to the safe design value.
[0004] Air purifier is a key device used to remove impurities such as water vapor and carbon dioxide in the air separation process to ensure the normal operation of the air separation unit. At present, the adsorbents filled in air purifiers are mostly double-layer structures of molecular sieve and alumina or single-layer structures filled with molecular sieve alone. When the molecular sieve adsorbs water vapor and carbon dioxide, there is a competitive adsorption relationship between the two. When the two coexist, the molecular sieve will adsorb more water molecules to occupy the active sites and lose the adsorption effect, resulting in poor carbon dioxide adsorption effect. Summary of the invention
[0005] The object of the present invention is to provide a molecular sieve adsorbent and a preparation method and application thereof. The molecular sieve adsorbent prepared by the method provided by the present invention has excellent water resistance and carbon dioxide adsorption effects.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a molecular sieve adsorbent, comprising the following steps:
[0008] Mixing sodium-based X-type molecular sieve raw powder, a binder and a porogen to obtain a powder; the binder is attapulgite; the sodium-based X-type molecular sieve raw powder has a silicon-aluminum ratio of 1.9 to 2.15;
[0009] The powder and the polymer solution are mixed and sphericalized to obtain an adsorbent precursor;
[0010] The adsorbent precursor is calcined to obtain the molecular sieve adsorbent.
[0011] Preferably, the sodium ion exchange degree of the sodium-based X-type molecular sieve raw powder is above 99.5%; the sodium-based X-type molecular sieve raw powder accounts for 76% to 84% of the total mass of the sodium-based X-type molecular sieve raw powder and the binder;
[0012] The silicon-aluminum ratio of the binder is 8 to 12; the binder accounts for 16% to 24% of the total mass of the sodium-based X-type molecular sieve raw powder and the binder;
[0013] The porogen includes starch and / or bran; the mass ratio of the porogen to the total mass of the sodium-based X-type molecular sieve raw powder and the binder is 0.3% to 1.0%;
[0014] The polymer in the polymer solution is polyacrylic acid and / or polymethacrylic acid; the mass percentage of the polymer in the polymer solution is 3‰ to 10‰; the mass ratio of the polymer solution to the total mass of the sodium-based X-type molecular sieve raw powder and the binder is 14% to 20%.
[0015] Preferably, the raw material of the powder further includes a reinforcing agent; the reinforcing agent is glass fiber; the ratio of the mass of the reinforcing agent to the total mass of the sodium-based X-type molecular sieve raw powder and the binder is 3‰ to 8‰.
[0016] Preferably, the spheronization is ball rolling; the spheronization equipment includes a sugar coating machine or a disc ball forming machine; the rotation speed of the spheronization equipment is 32-38 r / min.
[0017] Preferably, after the spheroidization, the process further comprises: mixing the adsorbent precursor and the surface finishing powder to perform surface shaping;
[0018] Calculated by mass percentage, the surface finishing powder comprises 70% to 80% of attapulgite and 20% to 30% of glass glaze; the mass ratio of the adsorbent precursor to the surface finishing powder is 4% to 6%.
[0019] Preferably, the vacuum degree of the calcination is below -0.05 MPa, the insulation temperature is 545°C to 565°C, the insulation time is 40 to 100 min, and the time for heating to the insulation temperature is 200 to 410 min.
[0020] Preferably, the temperature rising process of the calcination includes: rising from 30°C to 90°C, which takes 30 to 60 minutes; rising from 90°C to 300°C, which takes 90 to 150 minutes; rising from 300°C to 425°C, which takes 40 to 100 minutes; rising from 425°C to the insulation temperature, which takes 40 to 100 minutes.
[0021] The present invention also provides a molecular sieve adsorbent obtained by the preparation method described in the above technical solution, wherein the molecular sieve adsorbent is in the form of porous microspheres; and the particle size of the molecular sieve adsorbent is 1.5 to 3.5 mm.
[0022] Preferably, the molecular sieve adsorbent has a silicon-to-aluminum ratio of 2.4 to 2.6 and a specific surface area of 540 to 620 m 2 / g, pore volume is 0.35~0.39cm 3 / g.
[0023] The present invention also provides the molecular sieve adsorbent obtained by the preparation method described in the above technical solution or the use of the molecular sieve adsorbent described in the above technical solution in air separation.
[0024] The present invention provides a method for preparing a molecular sieve adsorbent, comprising the following steps: mixing sodium-based X-type molecular sieve raw powder, a binder and a porogen to obtain a powder; the binder is attapulgite; the silicon-aluminum ratio of the sodium-based X-type molecular sieve raw powder is 1.9 to 2.15; mixing the powder with a polymer solution, spheroidizing, and obtaining an adsorbent precursor; calcining the adsorbent precursor to obtain the molecular sieve adsorbent. The preparation method provided by the present invention uses sodium-based X-type molecular sieve raw powder as a preparation raw material, and has excellent static carbon dioxide and static water adsorption properties; the binder uses attapulgite, which has both excellent pore structure and adhesion, which is conducive to improving the static water adsorption performance; the water in the precursor is removed by calcination to avoid high temperature and high humidity conditions, and the porogen and polymer added during mixing are removed at the same time, thereby further increasing the pore structure of the adsorbent, ensuring that the finished adsorbent has excellent carbon dioxide adsorption performance under water vapor conditions. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing a molecular sieve adsorbent, comprising the following steps:
[0026] Mixing sodium-based X-type molecular sieve raw powder, a binder and a porogen to obtain a powder; the binder is attapulgite; the sodium-based X-type molecular sieve raw powder has a silicon-aluminum ratio of 1.9 to 2.15;
[0027] The powder and the polymer solution are mixed and sphericalized to obtain an adsorbent precursor;
[0028] The adsorbent precursor is calcined to obtain the molecular sieve adsorbent.
[0029] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.
[0030] The invention mixes sodium-based X-type molecular sieve raw powder, a binder and a porogen to obtain powder; the binder is attapulgite.
[0031] In the present invention, the sodium ion exchange degree (Na + / (Na + +K + )) can be above 99.5%, the silicon-aluminum ratio (SiO2 / Al2O3) can be 1.9-2.15, and in a specific embodiment, it can be 2 or 2.1; the sodium-based X-type molecular sieve raw powder can account for 76%-84% of the total mass of the sodium-based X-type molecular sieve raw powder and the binder, and in a specific embodiment, it can be 76%, 78%, 80%, 82% or 84%.
[0032] In the present invention, the binder is attapulgite, and in a specific embodiment, it can be domestic attapulgite and / or imported attapulgite; the silicon-aluminum ratio (SiO2 / Al2O3) of the binder can be 8-12, and in a specific embodiment, it can be 8, 9.5, 10.5 or 12; the binder can account for 16% to 24% of the total mass of the sodium-based X-type molecular sieve raw powder and the binder, and in a specific embodiment, it can be 16%, 18%, 20%, 22% or 24%. In the present invention, the binder is attapulgite, which has excellent pore structure and adhesion, which is beneficial to improving the static water adsorption performance. The richer the pores of the molecular sieve adsorbent material, the better the water absorption. The use of attapulgite as a binder can enable the adsorbent provided by the present invention to achieve simultaneous adsorption and co-adsorption of CO2 and water.
[0033] In the present invention, the porogen may include starch and / or bran; the starch may be corn starch and / or wheat starch; the ratio of the mass of the porogen to the total mass of the sodium-based X-type molecular sieve raw powder and the binder may be 0.3% to 1.0%, and in a specific embodiment, may be 0.4% or 0.5%. In the present invention, the porogen can be removed after calcination, further increasing the pore structure of the adsorbent, and ensuring that the finished adsorbent has excellent carbon dioxide adsorption performance under water vapor conditions. Limiting the amount of the porogen to the above range can avoid the problem of the adsorbent being easily broken.
[0034] In the present invention, the raw material of the powder may further include a reinforcing agent; the reinforcing agent may be glass fiber, and in a specific embodiment, may be quartz glass fiber; the silica content of the quartz glass fiber may be more than 99%, the length may be 70-120 μm, and the diameter may be 2-4 μm; the ratio of the mass of the reinforcing agent to the total mass of the sodium-based X-type molecular sieve raw powder and the binder may be 3‰-8‰, and in a specific embodiment, may be 3‰, 4‰, 6‰ or 8‰. The reinforcing agent in the present invention can make the adsorbent have a structure similar to a steel cage, so that the adsorbent has anti-expansion and anti-compression properties, and limiting the amount to the above range can avoid negative effects on the adsorption amount.
[0035] In the present invention, the polymer in the polymer solution may be polyacrylic acid and / or polymethacrylic acid; the mass percentage of the polymer in the polymer solution is 3‰ to 10‰, and in a specific embodiment, it may be 3‰, 5‰, 8‰ or 10‰; the mass ratio of the polymer solution to the total mass of the sodium-based X-type molecular sieve raw powder and the binder may be 14% to 20%, and in a specific embodiment, it may be 14%, 17% or 20%. In the present invention, the polymer can be removed after calcination, which further increases the pore structure of the adsorbent, ensures that the finished adsorbent has excellent carbon dioxide adsorption performance under water vapor conditions, and accelerates the adsorption rate.
[0036] The present invention does not have any special limitation on the mixing process, and the powder can be evenly distributed in a manner well known to those skilled in the art.
[0037] After obtaining the powder, the present invention mixes the powder with a polymer solution and performs sphericalization to obtain an adsorbent precursor.
[0038] In the present invention, the mixing may be performed by adding the mixed powder and the polymer solution at the same time during spheronization; the spheronization may be performed in a spheronization device; the spheronization is performed by rolling ball forming; the spheronization device includes a sugar coating machine or a disc spheronization machine; the rotation speed of the spheronization device may be 32 to 38 r / min, and in a specific embodiment, may be 34 r / min or 36 r / min.
[0039] In the present invention, the water content of the adsorbent precursor may be 36% to 42%, and in a specific embodiment, may be 36%, 38%, 40% or 42%; the particle size may be 1.5 to 5 mm, and in a specific embodiment, may be 2 mm, 3 mm or 4 mm.
[0040] In the present invention, after the spheroidization, the process may further include: mixing the adsorbent precursor and the surface finishing powder to perform surface finishing.
[0041] In the present invention, the surface finishing powder may include 70% to 80% attapulgite and 20% to 30% glass glaze, measured in percentage by mass. In a specific embodiment, it may be 70% attapulgite and 30% glass glaze, 75% attapulgite and 25% glass glaze, or 80% attapulgite and 20% glass glaze. The glass glaze is a white powdery inorganic silicate high-temperature calcined compound, which may be synthesized from Zn-Al-BK-Na-Si-Ca-O at high temperature. The mass ratio of the adsorbent precursor to the surface finishing powder may be 4% to 6%. The mixing method may be to sprinkle surface finishing powder on the surface of the adsorbent precursor; the adsorbent precursor may be a pre-wetted adsorbent precursor; the pre-wetting method may be to spray water mist on the surface of the adsorbent precursor; the spraying of water mist may be carried out under stirring conditions; the water mist may be deionized water mist; the mixing may be carried out in a sugar coating machine; the surface shaping may be surface curing; the surface curing time may be 15 to 35 minutes, and in a specific embodiment, may be 15 minutes, 28 minutes or 35 minutes. The glass glaze in the surface finishing powder of the present invention is combined with the reinforcing agent to make the adsorbent have a structure similar to a steel cage, so that the adsorbent has anti-expansion and anti-compression properties.
[0042] After obtaining the adsorbent precursor, the present invention calcines the adsorbent precursor to obtain the molecular sieve adsorbent.
[0043] In the present invention, drying may be further included before calcination; the drying temperature may be 80 to 180°C, and in a specific embodiment, may be 80°C, 100°C, 130°C, 150°C or 180°C; the drying time may be 1 to 2 hours; the vacuum degree of calcination may be below -0.05MPa, and in a specific embodiment, may be -0.05MPa, -0.07MPa or -0.08MPa; the holding temperature may be 545°C to 565°C, and in a specific embodiment, may be 550°C or 560°C; the holding time may be 40 to 100min, and in a specific embodiment, may be The time for heating to the insulation temperature can be 40min, 70min or 100min; the time for heating to the insulation temperature can be 200-410min. In a specific embodiment, the calcination process can be: 30°C to 90°C, 30-60min; 90°C to 300°C, 90-150min; 300°C to 425°C, 40-100min; 425°C to the insulation temperature, 40-100min; the calcination can be carried out in a muffle furnace; the calcination can also include cooling; the cooling can be natural cooling; the natural cooling can be carried out in a dryer. The above-mentioned limitation of the heating process in the present invention can slowly dehydrate the adsorbent and avoid the decrease of adsorption performance.
[0044] The preparation method provided by the present invention adopts sodium-based X-type molecular sieve raw powder as a preparation raw material, and has excellent static carbon dioxide and static water adsorption performance; the binder adopts attapulgite, which has both excellent pore structure and adhesion, and is conducive to improving the static water adsorption performance; the moisture in the precursor is removed by roasting to avoid high temperature and high humidity conditions, and the porogen and polymer added during mixing are removed at the same time, thereby further increasing the pore structure of the adsorbent, ensuring that the finished adsorbent has excellent carbon dioxide adsorption performance under water vapor conditions.
[0045] Furthermore, in the preparation method provided by the present invention, the binder itself has excellent pore structure and adhesion; the glass glaze in the surface finishing powder is combined with the reinforcing agent to make the adsorbent have a structure similar to a steel cage, so that the adsorbent has anti-expansion and anti-compression properties; the porogen and polymer added during the mixing are removed by roasting, thereby further increasing the pore structure of the adsorbent. The above factors are combined to make the adsorbent have both anti-expansion and anti-compression properties, and the shell breaking rate after freezing treatment is ≤1% (by weight), and it has excellent low temperature resistance, avoiding the phenomenon of crushing or powdering during the pressure release process when used in the purifier.
[0046] The present invention also provides a molecular sieve adsorbent obtained by the preparation method described in the above technical solution, wherein the molecular sieve adsorbent is in the form of porous microspheres; and the particle size of the molecular sieve adsorbent is 1.5 to 3.5 mm.
[0047] In the present invention, the silicon-aluminum ratio of the molecular sieve adsorbent can be 2.4-2.6, and in a specific embodiment, it can be 2.5; the specific surface area is 540-620m 2 / g, in a specific embodiment, it can be 560m 2 / g or 600m 2 / g; pore volume is 0.35~0.39cm 3 / g, in a specific embodiment, it can be 0.37cm 3 / g.
[0048] The molecular sieve adsorbent provided by the present invention has an X-type molecular sieve crystal structure, a static carbon dioxide adsorption capacity (25°C, 2.5mmHg)>7%, a static carbon dioxide adsorption capacity (25°C, 250mmHg)>19%, a static water adsorption capacity (25°C, RH75%)>28%, a shell breakage rate after freezing treatment of ≤1%, and has water resistance when adsorbing carbon dioxide.
[0049] The present invention also provides the molecular sieve adsorbent obtained by the preparation method described in the above technical solution or the use of the molecular sieve adsorbent described in the above technical solution in air separation.
[0050] In the present invention, activation may be further included before the air separation.
[0051] In the present invention, the air separation may be the adsorption of carbon dioxide and / or water vapor.
[0052] In order to further illustrate the present invention, the molecular sieve adsorbent provided by the present invention and its preparation method and application are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0053] Example 1
[0054] (1) 1 kg of polyacrylic acid is added into 200 kg of deionized water, wherein the average viscosity-average molecular weight of the polyacrylic acid is 450,000, and stirred at room temperature for 15 minutes to obtain a polymer solution, which is used as a molding liquid.
[0055] (2) Take 40 kg of sodium-based X-type molecular sieve raw powder, 9.97 kg of attapulgite binder (accounting for 20% of the total weight of the sodium-based X-type molecular sieve raw powder and the binder), 0.24 kg of reinforcing agent glass fiber, and 0.2 kg of pore structure modifier corn starch, wherein the sodium ion exchange degree of the X-type molecular sieve raw powder is 99.7%, the silicon-aluminum ratio is 2.05, and the silicon-aluminum ratio of the attapulgite is 10.5. The four raw materials are mixed in a mixer to obtain a mixed powder. The mixed powder is added to a pelletizing device while adding 13 kg of the molding liquid obtained in step 1 to obtain an adsorbent precursor with a diameter of 1.6 to 2.5 mm and a water content of 36%.
[0056] (3) 21 kg of adsorbent precursor is added to a sugar coating machine. Under the condition of rotation at 34 r / min, 0.2 kg of deionized water is sprayed into the machine to pre-wet the surface of the adsorbent precursor. Then, 0.9 kg of surface finishing powder is sprinkled on the wetted surface of the adsorbent precursor. The surface finishing powder includes 78% attapulgite and 22% glass glaze. The sugar coating machine is continued to rotate until the surface color is uniform and solidified to obtain a surface-finished adsorbent precursor.
[0057] (4) The surface-modified adsorbent precursor was dried at 150°C for 1 hour and then placed in a vacuum muffle furnace for programmed temperature increase. The vacuum degree was -0.07 MPa. The temperature increase program was: 30°C to 90°C, which took 60 min; 90°C to 300°C, which took 120 min; 300°C to 425°C, which took 80 min; 425°C to 550°C, which took 80 min. The temperature was kept at this temperature for 60 min and then cooled naturally to obtain a high-efficiency, water-resistant molecular sieve adsorbent.
[0058] Example 2
[0059] A high-efficiency water-resistant molecular sieve adsorbent was prepared according to the method of Example 1, except that the amount of polyacrylic acid added was 1.2 kg; the amount of attapulgite added as a binder was 11.2 kg (accounting for 23% of the total weight of the sodium-based X-type molecular sieve raw powder and the binder).
[0060] Example 3
[0061] An efficient and water-resistant molecular sieve adsorbent was prepared according to the method of Example 1, except that the amount of the binder attapulgite added was 8.79 kg (accounting for 19% of the total weight of the sodium-based X-type molecular sieve original powder and the binder); the drying temperature of the precursor was 120°C, the vacuum degree of the muffle furnace was -0.08 MPa, and the heating program was: 30-90°C, 60 min; 90°C-300°C, 130 min; 300°C-425°C, 80 min; 425°C-550°C, 60 min; 550°C-550°C, 70 min.
[0062] Example 4
[0063] A high-efficiency water-resistant molecular sieve adsorbent was prepared according to the method of Example 1, except that step (3) was not performed.
[0064] Example 5
[0065] A high-efficiency water-resistant molecular sieve adsorbent was prepared according to the method of Example 1, except that the vacuum degree of the muffle furnace was -0.04 MPa.
[0066] Example 6
[0067] A high-efficiency water-resistant molecular sieve adsorbent was prepared according to the method of Example 1, except that the amount of the binder attapulgite added was 13.17 kg (accounting for 26% of the total weight of the X-type molecular sieve raw powder and the binder).
[0068] Example 7
[0069] A high-efficiency water-resistant molecular sieve adsorbent was prepared according to the method of Example 1, except that the amount of the binder attapulgite added was 6.62 kg (accounting for 15% of the total weight of the X-type molecular sieve raw powder and the binder).
[0070] Comparative Example 1
[0071] A cryogenic air separation molecular sieve is prepared, and the specific steps are as follows:
[0072] (1) The cryogenic air separation molecular sieve comprises the following raw materials in parts by weight: 70-83 parts of 13X molecular sieve raw powder, 17%-30% of a binder mixture, and the binder mixture is a mixture of white clay and attapulgite in a mass ratio of 1:1. The molar ratio of silicon dioxide to aluminum oxide in the 13X molecular sieve raw powder is 2.19:1, the binder mixture is a mixture of kaolin and bentonite in a mass ratio of 1:1, and the ratio of the average particle size of the binder mixture to the particle size of the 13X molecular sieve raw powder is 2.5:10.
[0073] (2) After mixing the 13X molecular sieve raw powder and the binder mixture, the mixture is stirred at a speed of 800 r / min for 30 minutes to form a mixture, and then the mixture is placed in a ball forming machine for granulation to obtain a molecular sieve blank, and then the molecular sieve blank is dehumidified at 200° C. to obtain a molecular sieve primary product with a water content of 20%, and then the molecular sieve primary product is blown and suspended in mid-air under dry air, and the molecular sieve primary product is calcined and activated at 680° C. to obtain a deep-cold air separation molecular sieve with an average particle size of 2 mm.
[0074] Comparative Example 2
[0075] A high-efficiency water-resistant molecular sieve adsorbent was prepared according to the method of Example 1, except that the silicon-aluminum ratio (SiO2 / Al2O3) of the X-type molecular sieve raw powder was 2.32.
[0076] Comparative Example 3
[0077] A high-efficiency water-resistant molecular sieve adsorbent was prepared according to the method of Example 1, except that the binder was kaolin, and the added amount was 10.35 kg (accounting for 21% of the total weight of the X-type molecular sieve raw powder and the binder).
[0078] Test Case
[0079] (1) The static carbon dioxide adsorption capacity (25°C, 250 mmHg and 25°C, 2.5 mmHg) of the molecular sieves prepared in Examples 1 to 7 and Comparative Examples 1 to 3 was analyzed using a microscopy adsorption instrument. The results are shown in Table 1.
[0080] (2) The static water adsorption capacity (25° C., RH 75%) of the molecular sieves prepared in Examples 1 to 7 and Comparative Examples 1 to 3 was analyzed using a constant temperature and humidity chamber. The results are shown in Table 1.
[0081] (3) The ball breakage rate of the molecular sieves prepared in Examples 1 to 7 and Comparative Examples 1 to 3 after freezing treatment was analyzed by weight method. The results are shown in Table 1.
[0082] (4) The sample freezing treatment conditions are as follows: first, the sample is saturated with water, then immersed in water for 30 min and the surface water is drained, then frozen at -15°C for about 1 h, and then placed in a 120°C oven for drying for about 1 h, and the above operation is repeated 10 times.
[0083] (5) Dynamic carbon dioxide adsorption performance of the sample: Take the adsorbent particles, crush and sieve them, weigh 20±0.1g of 20-40 mesh particles, and load them into a fixed bed reactor. Directly pass nitrogen gas at a flow rate of 2±0.05L / min, heat-treat and activate at 300±5℃ for 2 hours, then seal and cool to 25±1℃. Then pass nitrogen gas with a carbon dioxide concentration of 450±5ppm for adsorption penetration experiment, with a flow rate of 3±0.05L / min and an adsorption temperature of 15±1℃. The dynamic adsorption capacity of carbon dioxide is calculated by testing its adsorption penetration time, and the adsorption amount is calculated by the actual flow rate of carbon dioxide and the adsorption penetration time. The dynamic adsorption capacity of carbon dioxide is calculated by dividing the carbon dioxide adsorption amount by the total mass of the adsorbent.
[0084] (6) Test method for water resistance of samples during carbon dioxide adsorption: nitrogen is directly passed through a reactor containing a high-efficiency water-resistant molecular sieve adsorbent that has been tested for dynamic carbon dioxide adsorption performance, at a flow rate of 2±0.05 L / min, and heat-treated and activated at 105±2°C for 2 hours, and then sealed and cooled to 25±1°C. Then, saturated water vapor with a carbon dioxide concentration of 450±5 ppm is passed through for a water co-adsorption experiment, at a flow rate of 3 L±0.05 / min, and the adsorption temperature is 15±1°C. After adsorption breakthrough, activation regeneration is performed, and the water co-adsorption experiment is performed again. The dynamic adsorption capacity of carbon dioxide co-adsorbed with water is calculated by testing its tenth adsorption breakthrough time, and its adsorption amount is calculated from the actual flow rate of carbon dioxide and the tenth adsorption breakthrough time. The algorithm for the dynamic adsorption capacity of carbon dioxide co-adsorbed with water is the carbon dioxide adsorption amount divided by the total mass of the adsorbent.
[0085] Table 1 Index test results of Examples 1 to 7 and Comparative Examples 1 to 3
[0086]
[0087]
[0088] As can be seen from Table 1, the molecular sieve adsorbents provided by the present invention can achieve excellent adsorption effects, and the dynamic adsorption capacity of carbon dioxide co-adsorbed with water is higher than that of Comparative Examples 1 to 2. The dynamic adsorption capacity of carbon dioxide co-adsorbed with water by the deep cold air separation molecular sieve provided in Comparative Example 1 is ≤1.8%, and the dynamic adsorption capacity of carbon dioxide co-adsorbed with water by the molecular sieve adsorbent provided in Comparative Example 2 is ≤1.8%, so it cannot meet the requirements of the high-efficiency water-resistant molecular sieve adsorbent of the present invention.
[0089] In Examples 1 to 7, the static carbon dioxide adsorption capacity (25°C, 2.5 mmHg) of the molecular sieve adsorbents obtained in Examples 1 to 4 and Example 7 is greater than 7%, and the static carbon dioxide adsorption capacity (25°C, 250 mmHg) is greater than 19%, and the adsorption effect is more excellent; the molecular sieve adsorbents obtained in Examples 1 to 3 and Examples 5 to 7 have a crushing rate of less than 5% after freezing treatment, and the molecular sieve adsorbents obtained in Examples 1 to 3 and Examples 5 to 6 have a crushing rate of less than 1% after freezing treatment, and the mechanical properties are more excellent. The molecular sieve adsorbent provided in Comparative Example 3 has a crushing rate of 9.6% after freezing treatment, so it cannot meet the mechanical property requirements of the high-efficiency water-resistant molecular sieve adsorbent of the present invention.
[0090] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a molecular sieve adsorbent, characterized in that: The following steps are involved: Mixing sodium-based X-type molecular sieve raw powder, a binder and a porogen to obtain a powder; the binder is attapulgite; the sodium-based X-type molecular sieve raw powder has a silicon-aluminum ratio of 1.9 to 2.15; The powder and the polymer solution are mixed and sphericalized to obtain an adsorbent precursor; The adsorbent precursor is calcined to obtain the molecular sieve adsorbent.
2. The preparation method according to claim 1, characterized in that: The sodium ion exchange degree of the sodium-based X-type molecular sieve raw powder is above 99.5%; the sodium-based X-type molecular sieve raw powder accounts for 76% to 84% of the total mass of the sodium-based X-type molecular sieve raw powder and the binder; The silicon-aluminum ratio of the binder is 8 to 12; the binder accounts for 16% to 24% of the total mass of the sodium-based X-type molecular sieve raw powder and the binder; The porogen includes starch and / or bran; the mass ratio of the porogen to the total mass of the sodium-based X-type molecular sieve raw powder and the binder is 0.3% to 1.0%; The polymer in the polymer solution is polyacrylic acid and / or polymethacrylic acid; the mass percentage of the polymer in the polymer solution is 3‰ to 10‰; the mass ratio of the polymer solution to the total mass of the sodium-based X-type molecular sieve raw powder and the binder is 14% to 20%.
3. The preparation method according to claim 1, characterized in that: The raw materials of the powder also include a reinforcing agent; the reinforcing agent is glass fiber; the ratio of the mass of the reinforcing agent to the total mass of the sodium-based X-type molecular sieve original powder and the binder is 3‰ to 8‰.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The spheronization is ball rolling; the spheronization equipment includes a sugar coating machine or a disc ball forming machine; the rotation speed of the spheronization equipment is 32-38 r / min.
5. The preparation method according to claim 1, characterized in that: After the spheroidization, the method further comprises: mixing the adsorbent precursor and the surface finishing powder to perform surface finishing; The surface finishing powder comprises 70% to 80% of attapulgite and 20% to 30% of glass glaze; the mass ratio of the adsorbent precursor to the surface finishing powder is 4% to 6%.
6. The preparation method according to claim 1, characterized in that: The vacuum degree of the calcination is below -0.05MPa, the insulation temperature is 545°C to 565°C, and the insulation time is 40 to 100 minutes; the time for heating to the insulation temperature is 200 to 410 minutes.
7. The preparation method according to claim 1 or 6, characterized in that: The heating process of the calcination includes: heating from 30°C to 90°C, which takes 30 to 60 minutes; heating from 90°C to 300°C, which takes 90 to 150 minutes; heating from 300°C to 425°C, which takes 40 to 100 minutes; heating from 425°C to the insulation temperature, which takes 40 to 100 minutes.
8. The molecular sieve adsorbent obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The molecular sieve adsorbent is in the form of porous microspheres; the particle size of the molecular sieve adsorbent is 1.5 to 3.5 mm.
9. The molecular sieve adsorbent according to claim 8, characterized in that: The molecular sieve adsorbent has a silicon-aluminum ratio of 2.4 to 2.6 and a specific surface area of 540 to 620 m 2 / g, pore volume is 0.35~0.39cm 3 / g.
10. Use of the molecular sieve adsorbent obtained by the preparation method according to any one of claims 1 to 7 or the molecular sieve adsorbent according to claim 8 or 9 in air separation.
Citation Information
Cited By
Molecular sieve / polyacrylate spherical composite material for CO2 adsorption separation and preparation method thereof
CN120515392A